Textual Preferences for the Interpretation of Verses on Social Equality: Study of Wahbah al-Zuhaili's Interpretation in Tafsir al-Munir - Ahmad Bastari (Jurnal Semiotika Quran, 2024)
This article aims to find out Wahbah al-Zuhaili’s interpretation of the verses on social equality. This is motivated by the fact that al-Zuhaili, who lives in contemporary times, who should interpret contextually, has analyzed the verses on social equality textually. By using qualitative methods and descriptive-analytical data analysis, this article concludes that al-Zuhaili’s interpretation of verses relating to social equality tends to use a textual approach to verses. This can be found in the three examples of al-Zuhaili’s interpretation regarding the verses on social equality, namely equality between the people and leaders (referring to QS. al-Maidah [5]: 42), equality between the rich and poor (referring to QS. al-Nisa' [4]: ​​135), and equality between men and women (referring to QS. al-Hujurat [49]: 13). In interpreting these three main themes, al-Zuhaili reviews the verses textually in a coherent manner and does not discuss the importance of being fair, equal, moderate and not comparing people in the current context. Al-Zuhaili’s interpretation shows that even though he lived in contemporary times, in interpreting the Qur'an he did not adapt it to the social conditions that surrounded his life.